(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
Colonic carcinoma is one of the most common internal malignancies and is the second leading cause of deaths in United States. Methotrexate (MTX) is a drug of choice in the treatment of colon cancer. The aim of the present research work was to develop and characterize colon targeted pellets of MTX for treatment of colonic carcinoma. The product and process parameters were optimized by screening methods. Pellets were prepared by extrusion spheronization using microcrystalline cellulose (MCC) as spheronizing aid and ethyl cellulose (EC) as release retardant in different ratio. Based on the physical appearance, sphericity and % in vitro drug release, batch P17 containing EC: MCC (3:7) was optimized for core pellets. The site specificity was obtained by screening the coating polymers and by coating the core pellets with EudragitS100. The 32 full factorial design was applied in which airflow rate (X1) and coating time (X2) were the independent parameters and physical appearance (Y1) and time taken for 100% drug release (Y2) were selected as the dependent variables. From the results obtained, 6min of coating time and 60cm3 /min airflow rate was optimized. The batch B5 showed appropriate physical appearance and % in vitro drug release upto 17hr indicating sustained release property. The ex-vivo studies performed on rat colon indicated a significant relation with the in vitro drug release. The drug release followed Higuchi’s model indicating the diffusion pattern of drug release from the matrix of pellets. Thus, the coated pellets can be a good candidate for site specific delivery of MTX to colon by decreasing the gastric irritation and thus to improve bioavailability.